How Risky Are U.S. Corporate Assets? - DAVYDIUK, TETIANA; RICHARD, SCOTT; SHALIASTOVICH, IVAN; YARON, AMIR (Journal of Finance, 2023)
ABSTRACT We use market data on corporate bonds and equities to measure the value of U.S. corporate assets and their payouts to investors. In contrast to equity dividends, total corporate payouts are highly volatile, turn negative when corporations raise capital, and are acyclical. At the same time, corporate asset returns are similar to returns on equity, and both are exposed to fluctuations in economic growth. To reconcile this evidence, we argue that acyclical but volatile net repurchases mask the exposure of total payouts' cash components to economic growth risks. We develop an asset pricing framework to quantitatively illustrate this economic channel.